Molecular composition and decomposition stages of organic matter in a mangrove mineral soil with time. (31st December 2019) - Kida, Morimaru; Kondo, Miyuki; Tomotsune, Mitsutoshi; Kinjo, Kazutoshi; Ohtsuka, Toshiyuki; Fujitake, Nobuhide
Abstract: The molecular composition of soil organic matter (SOM) is important in understanding the elemental cycling of mangrove forests. The aim of the study was to investigate the SOM compositional changes with time in a mangrove mineral soil, which is rarely reported in the literature. A 1-m soil core was collected in the subtropical Fukido River mangrove forest (Okinawa, Japan) and separated into 25-cm sections. Humic acids (HA) and fulvic acids (FA) were extracted from the soil, and their relative abundance and chemical characteristics were analyzed by elemental analysis, stable carbon analysis, spectrophotometric measurement, liquid-state 13 C nuclear magnetic resonance spectroscopy, and radiocarbon dating. HA exhibited a clear depth trend in the chemical characteristics, with lower H/C and N/C ratios, higher aromaticity, and higher phenolic 13 C NMR peaks in the deeper sections. FA did not show such a clear depth trend, and was enriched in O-containing functional groups. A combination of radiocarbon dating and structural analysis of HA indicated that the rapid structural changes in HA (H/C and N/C) occurred during the first years–decades, followed by a gradual change over a time scale of several hundred ( 500) years, and these structural changes were best explained by an increase in the relative phenolic C contents. These results show that mangrove SOM is a complex mixture of organic fractions with different biogeochemical reactivities. Graphical abstract: Image 1 Highlights: We assessed SOM compositional changes with time ( 500 yrs) in a mangrove mineral soil. The compositional changes occurred as first rapid changes followed by later slow ones. An increase in the relative phenolic C contents best explained these two-step changes. Mangrove SOM is a complex mixture of organic fractions with different reactivities.